Mustangs - Michael Portman
The Ford Motor Company created one of the most influential cars of all time when it developed the Mustang. Readers see exactly how this car impacted the worlds of automobiles and popular culture. Modeled after the sports cars of Europe in the early 1960s, Mustangs have gone through many changes, but are still seen in car dealerships and on roads all across America. Vivid photographs show Mustangs throughout their history, and fun facts explain how they became one of the most important American cars ever developed.